High-sensitive MXene and GST-based tunable refractive index sensor for the infrared and visible spectrum from multipurpose sensing applications - Khadka, Kiran; Karki, Bhishma (Journal of Advanced Academic Research, 2024)
In this paper, a sensor with a multi-layered structure based on MXene and GST as an active plasmonic material is designed. The design is simulated in 2D. The design is a general sensor to detect refractive index from 1 to 1.14. Here, the design structure is arranged by placing the analyte on top. The middle metal layer is considered Ag/Au/Al/Cu to identify the effect of the metal layer on overall absorption and reflector. The GST layer is configured as a state material aGST and cGST, where the different properties of the states are considered for identification of the tunable behaviour of the structure. Optimisation and validation for parameters like height, width, and other metals, such as Ag/Au/Cu/Al processes, were conducted to ensure optimal device performance. The proposed refractive index sensor offers a high sensitivity variation ranging from 80 deg/RIU to 770 deg/RIU. Overall bandwidth and the resonating region are different for both phases of GST material. In other words, the proposed refractive index sensor can be used as a lab-on-chip biosensor.